Both orexin receptors are expressed in rat ovaries and fluctuate with the estrous cycle. Effects of orexin receptor antagonists on gonadotropins and ovulation - Silveyra, Patricia (2007)
Orexins are peptides controlling feeding, sleep, and neuroendocrine functions. They are synthesized by the hypothalamus with projections throughout the brain. Orexins and their orexin 1 (OX(1)) and orexin 2 receptors (OX(2)) are present outside the central nervous system. Here the expression of preproorexin (PPO), OX(1), and OX(2) was studied in rat ovaries. PPO, OX(1), and OX(2) were determined by quantitative real-time RT-PCR in ovaries of cycling Sprague-Dawley rats on all days of the cycle. Serum hormones and food consumption were determined. Ovarian OX(1) and OX(2) expression was then studied after ovulation blockade with Cetrorelix or Nembutal. Finally, proestrous rats were treated at 1400 and 1900 with a selective OX(1) antagonist (SB-334867-A) and/or a selective OX(2) antagonist (JNJ-10397049), and hormone levels, ovulation, and ovarian histology were studied. Both receptors' expression increased in the ovary between 1700 and 2300 of proestrus exclusively, in coincidence with hormone peaks, but not with the dark-light cycle or food intake. PPO was not detected. Cetrorelix or Nembutal prevented the increases of OX(1) and OX(2) while blunting gonadotropin peaks. SB-334867-A and JNJ-10397049, alone or combined, decreased serum gonadotropins and reduced ova number the following morning; ovaries showed a bloody (hyperemic and/or hemorrhagic) reaction with more preovulatory follicles and less corpora lutea. Here we demonstrate for the first time an increased ovarian expression of both OX(1) and OX(2), only during proestrous afternoon, and its hormone dependence but not dependence on the dark-light cycle. Two new receptor antagonists reduced proestrous gonadotropins and/or ova number while producing ovarian structural changes.